A non-human primate in vitro functional assay for the early evaluation of TB vaccine candidates - Tanner, R; White, AD; Boot, C; Sombroek, CC; O'Shea, MK; Wright, D; Hoogkamer, E; Bitencourt, J; Harris, SA; Sarfas, C; Wittenberg, R; Satti, I; et al. (Springer Nature, 2021)
We present a non-human primate mycobacterial growth inhibition assay (MGIA) using in vitro blood or cell co-culture with the aim of refining and expediting early tuberculosis vaccine testing. We have taken steps to optimise the assay using cryopreserved peripheral blood mononuclear cells, transfer it to end-user institutes, and assess technical and biological validity. Increasing cell concentration or mycobacterial input and co-culturing in static 48-well plates compared with rotating tubes improved intra-assay repeatability and sensitivity. Standardisation and harmonisation efforts resulted in high consistency agreements, with repeatability and intermediate precision <10% coefficient of variation (CV) and inter-site reproducibility <20% CV; although some systematic differences were observed. As proof-of-concept, we demonstrated ability to detect a BCG vaccine-induced improvement in growth inhibition in macaque samples, and a correlation between MGIA outcome and measures of protection from in vivo disease development following challenge with either intradermal BCG or aerosol/endobronchial Mycobacterium tuberculosis (M.tb) at a group and individual animal level.